A facile approach for controlled synthesis of hydrophilic starch-based nanoparticles from native sago starch - Tay, S.H.; Pang, S.C.; Chin, S.F. (WILEY-VCH Verlag GmbH & Co, 2012)
A facile approach for the preparation of hydrophilic starch-based spherical nanoparticles from native sago (Metroxylon sagu) starch using the drop-wise solvent exchange method was reported. Starch-maleate monoester (SM) was initially synthesized from native sago starch and maleic anhydride in an aqueous medium, and SM nanoparticles was subsequently precipitated in absolute ethanol under controlled conditions. The present study was focused mainly on modulating of the solvent and non-solvent systems to prepare SM nanoparticles of different morphologies. The pH of the solvent system and the nature of surfactants being added into the solvent system could influence the morphology of regenerated SM nanoparticles. SM nanoparticles of discrete and spherical shape were regenerated from a basic SM sample solution, or an acidic sample solution in the presence of an appropriate surfactant. SM nanoparticles with mean diameter of about 250 nm was obtained by precipitation in absolute ethanol in the presence of Brij 35 as the surfactant.